Effects of Continuous Laydown and Compaction on Interlayer Shear Bonding of Asphalt Layers - Haitao Zhang; Mingyang Gong; Jian Wu; Quansheng Sun (Advances in Materials Science and Engineering)
Traditional discontinuous paving technology of asphalt pavement is to pave and compact with two different gradation asphalt mixtures in the upper and lower layers, respectively, so the interlayer contact state of asphalt mixture is the major issue of pavement structure. Meanwhile, the continuous paving technology is to pave and compact with two different gradation asphalt mixtures in the upper and lower layers simultaneously, which can solve the issue of interlayer contact appropriately. In order to contrast the shear performance of the structural layer based on continuous and discontinuous paving technology, in this project, through simulating site construction, the double-deck Marshall and rut specimens are prepared based on two different gradation asphalt mixtures simultaneously, and the mechanical and interlayer shear performances of asphalt mixtures under continuous and discontinuous paving technology are tested at room temperature, low temperature, and freeze-thaw. The test results show that the mechanical and interlayer shear performance of continuous paving asphalt mixtures is better than that of discontinuous paving asphalt mixture. The findings can provide a certain technical basis for the design of continuous paving asphalt pavement.